1999
DOI: 10.1002/(sici)1098-2264(199912)26:4<286::aid-gcc2>3.3.co;2-o
|View full text |Cite
|
Sign up to set email alerts
|

Identification of germline missense mutations and rare allelic variants in the ATM gene in early‐onset breast cancer

Abstract: Epidemiological studies have shown an increased risk of breast cancer in obligate ataxia telangiectasia (A-T) heterozygotes. We analyzed 100 samples from young breast cancer patients for mutations in ataxia-telangiectasia mutated (ATM), the gene responsible for the autosomal recessive condition, A-T, to determine whether A-T heterozygosity predisposes such individuals to develop breast cancer. These patients were selected from families with a moderate or absent family history of breast cancer and included a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1

Year Published

2000
2000
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 28 publications
3
47
1
Order By: Relevance
“…This missense alteration has not been previously described as a polymorphism in the ATM mutation database (http://www.benaroyaresearch.org/bri_investigators/ atm.htm). It has been reported as a rare variant (allele frequency 0.015) by Izatt et al (1999), and found in the heterozygous state in four out of 65 individuals of North African origin (Hall, unpublished data), and thus was considered as an ATM polymorphism in this present study. LCLs were routinely maintained at 371C, in a humidified incubator with 5% CO 2 , in exponential growth by dilution twice a week to 5 Â 10 5 cells ml À1 in RPMI1640 medium (Gibco, Invitrogen Corporation, Cergy-Pontoise, France) supplemented with 10% heat-inactivated foetal calf serum (Integro b.v, Zaandan, Holland) and penicillin and streptomycin (100 mg ml À1 , Gibco).…”
Section: Cell Linesmentioning
confidence: 67%
“…This missense alteration has not been previously described as a polymorphism in the ATM mutation database (http://www.benaroyaresearch.org/bri_investigators/ atm.htm). It has been reported as a rare variant (allele frequency 0.015) by Izatt et al (1999), and found in the heterozygous state in four out of 65 individuals of North African origin (Hall, unpublished data), and thus was considered as an ATM polymorphism in this present study. LCLs were routinely maintained at 371C, in a humidified incubator with 5% CO 2 , in exponential growth by dilution twice a week to 5 Â 10 5 cells ml À1 in RPMI1640 medium (Gibco, Invitrogen Corporation, Cergy-Pontoise, France) supplemented with 10% heat-inactivated foetal calf serum (Integro b.v, Zaandan, Holland) and penicillin and streptomycin (100 mg ml À1 , Gibco).…”
Section: Cell Linesmentioning
confidence: 67%
“…However, a non-conservative amino acid change H1380Y (C4138T) was discovered that lies directly within the Abl-binding motif DPAPNPPHFP in exon 30 and two samples had a nearby rare polymorphism, C4258T, causing a non-conservative amino acid change (L1420F) that has been reported previously. 22,23 Both nucleotide changes detected in the CML samples appeared to have arisen on one allele.…”
Section: Discussionmentioning
confidence: 97%
“…No missense mutations were screened for in the present study. There are, however, several reports on germline amino acid substitutions in breast cancer patients with frequencies ranging from 7-41% (Vorechovsky et al, 1996a(Vorechovsky et al, , 1996bAppleby et al, 1997;Larson et al, 1998;Shayeghi et al, 1998;Izatt et al, 1999). Gatti et al (1999) hypothesize that both heterozygotes and homozygotes for the two types of ATM mutations, the truncating (ATM trunc ), resulting in no protein or truncated protein, and the missense (ATM mis ) resulting in reduced amounts of defective protein, may give different phenotypes.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with Vorechovsky et al (1996b). Recently, Izatt et al (1999) reported loss of the wild type allele in five breast cancer patients carrying different missense substitutions in the ATM protein, suggesting that LOH coincides with ATM missense mutations in breast cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation